A Structured Survey on Adverse Events Occurring Within 24 Hours After Intravenous Exposure to Gadodiamide or Gadoterate Meglumine: A Controlled Prospective Comparison Study. Issue 4 (April 2019) - Parillo, Marco; Sapienza, Martina; Arpaia, Francesco; Magnani, Francesca; Mallio, Carlo Augusto; D'Alessio, Pasquale; Quattrocchi, Carlo Cosimo
Abstract : Objective: This study compares the incidence of new-onset symptoms within 24 hours after enhanced magnetic resonance imaging (eMRI) with intravenous administration of gadodiamide or gadoterate meglumine compared with a control group undergoing unenhanced MRI (uMRI). Materials and Methods: A prospective cohort study (n = 1088 patients) was designed to assess the incidence of symptoms within 24 hours after administration of gadodiamide or gadoterate meglumine. The participants underwent a structured questionnaire by phone call before and 24 hours after the MRI scan to check for symptoms that were not present before the scan. The questionnaire included a list of active questions aimed to test the prevalence of symptoms that have been proposed in the debated definition of gadolinium deposition disease (GDD) and that we recorded in this study as GDD-like. In particular, the following symptoms and signs were tested: central torso pain, arm or leg pain, bone pain, headache, skin redness (any site of the body), fatigue, and mental confusion. Fisher exact test was used to test differences between groups with significance threshold set at P < 0.05. Results: Within the 24 hours after the MRI scan, 8.3% of patients reported at least one new-onset symptom in the uMRI group versus 17.4% in the gadodiamide eMRI versus 17.8% in the gadoterate meglumine eMRI group. The difference between the eMRI and the uMRI group was statistically significant ( P < 0.001 for gadodiamide and P < 0.001 for gadoterate meglumine). There was not a different incidence of symptoms between the gadodiamide and the gadoterate meglumine eMRI groups. For gadodiamide, fatigue ( P < 0.05) and dizziness ( P < 0.05) were symptoms significantly more frequent than uMRI group; for gadoterate meglumine, fatigue ( P < 0.01), mental confusion ( P < 0.01), and diarrhea ( P < 0.01) were significantly more frequent than uMRI group. Conclusions: We found that the onset of new symptoms within 24 hours after exposure to gadolinium-based contrast agent was more frequent than after uMRI. Among GDD-like symptoms, fatigue and mental confusion were the most frequent symptoms reported after eMRI. The other GDD-like symptoms were not overreported after eMRI versus uMRI. Thus, these results are questioning the term GDD.